Study on the Effect of Masticatory Frequency on One Hour Postprandial Blood Sugars in Normoglycemic and Dysglycemic Individuals - Mani Mohan K P Reddy; S V Srinivasa (Journal of Clinical and Biomedical Sciences)
Background: The best method of prevention of diabetes includes early detection and dietary modifications through which the disease progression could be controlled in the modern era a novel yet sustained lifestyle modification is needed in preventing the progression of the disease. Mastication frequency has a role to play on glycaemic parameters in individuals, especially in the prandial phase. Aims: The study focuses on the effect of masticatory frequency on one hour post prandial sugars (since one hour post prandial blood sugars have a better prognostic value in predicting disease progression) in dysglycemic individuals as an attempt to prove the effectiveness of masticatory frequency as a dietary modification in dysglycemic. Results: A study group of 160 individuals divided into two groups of dysglycemic and normoglycemic. It is found that increased mastication frequency has a bearing on the post prandial sugars significantly in normoglycemic individuals. Conclusion: Thus can be used s a lifestyle modification in preventing the progression of the disease Keywords Lifestyle modification, Diabetic mellitus, Treatment, Dysglycemic, Normoglycemic, Postprandial blood sugar